Contextualization And Entextualization Mandarese Patriotism In Kalindaqdaq Pettomuaneang Performance - Rabiatul Adawiah; Srimusdikawati Srimusdikawati (Jurnal Adabiyah: Humanities and Islamic Studies, 2019)
Kalindaqdaq is one literary work of Mandarese, the majority ethnic in West Sulawesi. It is categorized as an old poem, and nowadays Kalindaqdaq is only shown in a few cultural events. The objective of this research is to explore Mandarese local wisdom related to patriotism through contextualizing and entextualizing Kalindaqdaq Pettomuaneang. This research used a qualitative method with two approaches; systemic functional and ethnographical approach. The result shows that the emergence of Kalindaqdaq Pettomuaneang was influenced by the political situation. Based on its contextualization, there are three characteristics of an ideal leader. They must have sincerity, consistency, and firmness. Next, intextuality involved some contexts. Texts in manetteq context are decontextualized such as manetteq (weave), lipaq (sarong), bannang pute (white yarn), lango-lango (dye), sureq (motif), and pucca (center of motif), and after that, they are recontextualized in patriotism as its new context. Leadership is seen as the same as weaving process, not only be carefulness, a good leader should be creative. So seeing the success of contextualization and entextualization in Kalindaqdaq Pettomuaneang, it can be concluded that Mandarese is ethnic with high cognitive characteristics. Because of to do contextualization and entextualization, people should have specific competence in language and logic.